The Sonographic Appearance of Seminal Megavesicles, an Association With Autosomal Dominant Polycystic Kidney Disease: A Series Review. (July 2021) - Carr, Georgia
Megavesicles are an uncommon diagnostic finding during sonography of the bladder, especially when the examination is performed transabdominally. Although megavesicles are more likely seen with transrectal ultrasonography, computed tomogram (CT), vesiculography, or magnetic resonance imaging (MRI), it has been noted during transabdominal sonography for patients suffering from autosomal dominant polycystic kidney disease (ADPKD). When seminal vesicles become dilated, they are often visualized during transabdominal sonography. Two patient cases are provided of seminal megavesicles, associated with ADPKD and have documented sonographic findings. Both patient cases of megavesicles were discovered incidentally during the course of a renal sonogram. The importance of these diagnostic findings and the possible pathogenesis are provided.